HUBUNGAN ANTARA PENGETAHUAN DENGAN PENCEGAHAN TUBERKULOSIS PARU OLEH KELUARGA DI SUMBA BARAT - Fiane de Fretes; David Kondi (Jurnal Ilmu Keperawatan Medikal Bedah, 2022)
Family is one of the support systems to deliver health care during Tb Treatment. Families are involved as a Pengawas Minum Obat (PMO), accompany patients during medical check up, financial support, fulfill nutritional needs, and prevent bacterial transmission among family members. Preventing behaviour of Tuberculosis including maintaining personal hygiene, maintaining the environment, and Bacillus Calmette-Guerin (BCG) Immunization. The involvement of the family is proposing to decrease the decline of Tb incidence. However, there are eight (8) patients who do not comply with Tb treatment in 2018, increasing from the previous year. The aim of this research is to find a relationship among family knowledge about Tb with preventing Tb in West Sumba. The sampling method is using purposive sampling technique to 100 people in pre-research term, then the obtained data will be analyzed using Completely Randomized Design (CRD), and the conclusion will be drawn with 5% of meaningfulness interval. Validity and reliability of the questionnaire will be tested through SPSS Statistic version 25 software. This study that analyzed by Completely Randomized Design (CRD), shows that respondents had known the information related to pulmonary tuberculosis seen from the Fcount is greater than the Ftable with significant levels of 5% and 1%, while on the prevention of transmission of pulmonary tuberculosis didn’t show its relationship as seen from the Fcount is smaller than the Ftable with significant levels of 5% and 1%. Hence, from this study it can be concluded that even respondents had known the information related to pulmonary tuberculosis, but families in West Sumba had not done prevention towards pulmonary tuberculosis transmission.